Insight into the electrical properties and chain conformation of spherical polyelectrolyte brushes by dielectric spectroscopy. (12th December 2016) - Guo, Xiaoxia; Zhao, Kongshuang
Abstract: We report here a dielectric study on three kinds of anionic spherical polyelectrolyte brush (SPBs, consisting of a polystyrene (PS) core and three different poly (acrylic acid) chains grafted onto the core) suspensions over a frequency ranging from 40 Hz to 110 MHz. The relaxation behavior of the SPB suspensions shows significant changes in the brush-layer properties when the mass fraction of SPBs and the pH of the suspensions change. Two definite relaxations related to the interfacial polarization are observed around 100 kHz and 10 MHz. A single-layer spherical-shell model is applied to describe the SPB suspensions wherein the suspended SPB is modeled as a spherical-shell composite particle in which an insulated PS sphere is surrounded by a conducting ion-permeable shell (the polyelectrolyte chain layer). We developed the curve-fitting procedure to analyze the dielectric spectrum in order to obtain the dielectric properties of the components of the SPBs, especially the properties of the polyelectrolyte brush. Based on this method and model, the permittivity and conductivity of the brush layer, ζ potential, etc are calculated. The ordered orientation of the water molecules in the layer leads to an additional electrical dipole moment; increasing pH causes the brush layer to swell. In addition, the repulsive force between the SPB particles are evaluated using the brush-layer thickness, which is obtained by fitting dielectric spectra, combined with relative theoretical formulas. Increasing PH values or SPB concentration would improve the stability of the SPBs dispersion.